2018
DOI: 10.1103/physrevapplied.10.024053
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Holographic Microscopy Exploiting Speckle-Correlation Scattering Matrix

Abstract: Using conventional refraction-based optical lens, it is challenging to achieve both high-resolution imaging and long-working-distance condition. To increase the numerical aperture of a lens, the working distance should be compensated, and vice versa. Here we propose and demonstrate a new concept in optical microscopy that can achieve both high-resolution imaging and long-working-distance conditions by utilising a scattering layer instead of refractive optics. When light passes through a scattering layer, it cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…q(s) = arcsin |T n (s)| |T n (s)| max (21) and T n is the desired function to be encoded (for example Eqs. (14), (15) and (22)) and φ g is a linear phase ramp which defines the period and angle of the resulting grating.…”
Section: Modal Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…q(s) = arcsin |T n (s)| |T n (s)| max (21) and T n is the desired function to be encoded (for example Eqs. (14), (15) and (22)) and φ g is a linear phase ramp which defines the period and angle of the resulting grating.…”
Section: Modal Decompositionmentioning
confidence: 99%
“…Such wavefront sensing techniques rely on the ability to measure the phase of light which can only be indirectly inferred from intensity measurements. Methods to do so include ray tracing schemes, intensity measurements at several positions along the beam path, pyramid sensors, interferometric approaches, computational approaches, the use of non-linear optics, computer generated holograms (CGHs), meta-materials and polarimetry [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Perhaps the most well-known is the Shack-Hartmann wavefront sensor [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…There are many existing methods to achieve high-resolution imaging, such as wavefront engineering [50], speckle correlations based on speckle correlations via non-invasive imaging through scattering layers [51,52], and a transmission matrix [53]. Recently, multiple computational imaging approaches have been demonstrated, including phase-space measurements [54,55], wavefront sensing with the Demon algorithm [56], and the speckle-correlation scattering matrix (SSM) [57,58]. For the conventional scattering media (CSM), lots of limitations still exist for practical applications in the real world, such as the stability of optical properties [59] and incomplete channel control in multiple scattering [60].…”
Section: Computational Optics Based On Metasurfacementioning
confidence: 99%
“…Secondly, it utilizes the universal statistical property of the speckle phenomenon without a priori information or volumetric data correction. Recent studies have shown that the SSM methods achieve holographic imaging and sensing through turbidity [51,52], which will pave the way for new applications in various spectral domains.…”
Section: Introductionmentioning
confidence: 99%